.NET and XML - Bornstein, Niel M. (Safari electronic books, 2003)
If you're seeking ways to build network-based applications or XML-based web services, Microsoft provides most of the tools you'll need. XML is integrated into the .NET Framework and Visual Studio .NET, but if you want to get a grasp on how .NET and XML actually work together, that's a different story. With .NET and XML, you can get under the hood to see how the .NET Framework implements XML, giving you the skills to write understandable XML-based code that interoperates with code written with other tools, and even other languages. .NET and XML starts by introducing XML and the .NET Framework, and then teaches you how to read and write XML before moving on to complex methods for manipulating, navigating, transforming, and constraining it. To demonstrate the power of XML in .NET, author Niel Bornstein builds a simple hardware store inventory system throughout the book. As you move from chapter to chapter, you'll absorb increasingly complex information until you have enough knowledge to successfully program your own XML-based applications. This tutorial also contains a quick reference to the API, plus appendices present additional .NET assemblies that you can use to work with XML, and how to work with the .NET XML configuration file format. One study puts the potential market for new software based on XML at or near $100 billion over the next five years. The .NET Framework gives you a way to become a part of it. But to use XML and .NET effectively, you need to understand how these two technologies work together. This book gives you the insight to take full advantage of the power the two provide.